Faktor yang Berhubungan dengan Long-term COVID-19: Studi Observasi Cross-Sectional di Indonesia - Arina Dery Puspitasari; Nanda Ardianto; Lily Aina; Eunice Marlene Sicilia Kundiman; Fatimatuz Zahra Oviary Satryo; Melinda Putri Amelia Rachman; Fauzul Meiliani; Pharmasinta Putri Hapsari; Bambang Subakti Zulkarnain; Alfian Nur Rosyid; Tamara Nur Budiarti; Brigitta Dhyah Kunthi Wardhani (Warmadewa University, 2022)
Long-term COVID-19 could occur in COVID-19 patients, affecting the patient's quality of life, and becoming a problem for public health. However, information is rarely on factors associated with the occurrence of long COVID-19 cases. This study analyzed factors associated with long-term COVID-19. The study was an observational cross-sectional, conducted in August 2021. The data were collected through a Google form questionnaire distributed to COVID-19 survivors in Indonesian. They must be aged more than 17 years to meet the inclusion criteria, while those with incomplete data were excluded. The data were processed by using SPSS 21 with an ordinal regression test in which an alpha level was 5%. As many as 101 from 16 men (15.8%) and 85 women (84.2%) were obtained. Comorbid status (p-value = 0.001) and duration of treatment (p-value = 0.034 and 0.015) had a significant association with the occurrence of long-term COVID-19. Meanwhile, age, gender, occupation, type of care, and vaccination status were not likely associated with long-term COVID-19. COVID-19 patients with comorbidity and a long duration of treatment are more likely to experience long-term COVID-19. Keywords: COVID-19, long-term COVID-19, factor, public health